2012
DOI: 10.1002/anie.201204169
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Biomacromolecules within Polymersomes by Electroporation

Abstract: Biological macromolecules can be encapsulated into preformed polymersomes by controlled temporary destabilization of the vesicle membrane. The morphology and the size of the polymersome are unchanged after electroporation, suggesting that the polymersome membrane is reformed. The surface charge of the biomacromolecules plays a key role for the electroporation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 22 publications
3
77
0
1
Order By: Relevance
“…and allow large amounts of biological molecules, alone and in combination, including proteins and nucleic acids, to be compartmentalized into nanoscale reactors (29,30). Furthermore, we have demonstrated (31)(32)(33)(34) that, when two different copolymers are used to form one polymersome, the resulting membrane segregates laterally into patterns whose topology is strictly controlled by the molar ratio of the two copolymers and eventually coarsen into two separate domains forming asymmetric polymersomes (35).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…and allow large amounts of biological molecules, alone and in combination, including proteins and nucleic acids, to be compartmentalized into nanoscale reactors (29,30). Furthermore, we have demonstrated (31)(32)(33)(34) that, when two different copolymers are used to form one polymersome, the resulting membrane segregates laterally into patterns whose topology is strictly controlled by the molar ratio of the two copolymers and eventually coarsen into two separate domains forming asymmetric polymersomes (35).…”
Section: Introductionmentioning
confidence: 85%
“…To a first approximation, we can thus infer that the PBO membrane is two orders of magnitude less permeable than the PDPA membrane. We can use such an asymmetric polymersome to encapsulate enzymes using a technique based on electroporation (30). We chose glucose oxidase to catalyze the glucose oxidation to form D-glucono-d-lactone and hydrogen peroxide and catalase to catalyze the decomposition of hydrogen peroxide into water and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…These polymersomes are formed through the self-assembly of amphiphilic copolymers in aqueous media, 7 and combine the advantages of long-term stability with the potential to encapsulate a broad range of cargoes. [8][9][10] We have previously demonstrated that the pH sensitive block copolymer poly(2-(methacryloyloxy) ethyl-phosphorylcholine)-co-poly(2-(diisopropylamino)ethyl methacrylate) (PMPC-PDPA) can combine specific cellular targeting efficiency (through the PMPC block and its affinity toward the scavenger receptor B1), 11 with effective endosomal escape and cytosolic delivery following internalisation (by the pH sensitive PDPA). 8,12 In this study, we describe the half life and bio-distribution of the PMPC-PDPA polymersomes in vivo, showing the dynamics of accumulation within different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of electroporation is largely unknown (mainly due to the short time scales and difficulty in probing pore formation), polymersome are believed to undergo similar poration to that observed in natural lipid cell membranes [40]. Furthermore, there are multiple parameters which can affect the outcome of electroporation.…”
Section: Forming Magnetopolymersomesmentioning
confidence: 99%